Pendampingan Kelompok Petani Muda dalam Upaya Menggali Potensi dan Kreativitas Desa Pada Masa Pandemi di Desa Sumberejo Kota Batu - Farah Mutiara; Eri Yusnita Arvianti; A. Yusuf Kholil (Universitas Tribhuwana Tunggadewi Malang, 2021)
WHO (World Health Organization) has declared the coronavirus a global pandemic. As one of the countries exposed and the pandemic, Indonesia has changed the lives of all people from various walks of life. It is hoped that the younger generation, as young, dynamic, full of energy, full of optimism, can bring changes that move and try to help the government in breaking the spread of COVID-19. One of them is the role of youth in the agricultural sector. The implementation method used to explore the potential and creativity of young farmers in Sumberejo Village is by providing counseling. The activities carried out are by introducing IT technology, training, and marketing counseling, and more modern business bookkeeping to youth. This activity is very suitable for the conditions of community social restrictions that are currently being carried out. The purpose of this activity is to provide knowledge to young farmers in Sumberejo Village so that the knowledge and skills of young farmers can increase in internet-based business bookkeeping, increase creativity in online marketing so that they are more motivated and good at reading opportunities, and increase the creativity of village youth during the pandemic. Covid-19 and the existence of social restrictions will not dampen their efforts in the organic vegetable business.ABSTRAKWHO (World Health Organization) menetapkan virus corona sebagai pandemi global. Indonesia sebagai salah satu negara yang terpapar dan adanya pandemi tersebut telah merubah kehidupan seluruh kalangan masyarakat dari berbagai lapisan. Diharapkan generasi muda sebagai sosok yang muda, dinamis, penuh energi, penuh optimis dapat membawa perubahan yang bergerak dan berusaha untuk membantu pemerintah dalam memutus penyebaran covid-19. Salah satunya yaitu peran pemuda di sektor pertanian. Metode pelaksanaan yang dipakai untuk menggali potensi dan kreativitas petani muda di Desa Sumberejo yaitu dengan memberikan penyuluhan. Kegiatan yang dilakukan yaitu dengan memberikan pengenalan teknologi IT, pelatihan dan penyuluhan pemasaran dan pembukuan usaha yang lebih modern kepada pemuda. Adanya kegiatan tersebut sangat cocok untuk kondisi pembatasan sosial masyarakat saat ini sedang dijalankan.Tujuan kegiatan ini yaitu dapat memberikan pengetahuan kepada petani muda di Desa Sumberejo sehingga pengetahuan dan keterampilan petani muda dapat meningkat dalam pembukuan usaha berbasis internet, meningkatkan kreativitas dalam pemasaran online sehingga mereka lebih termotivasi dan pandai membaca peluang dan meningkatkan kreativitas pemuda desa di masa pandemi. covid-19 dan adanya pembatasan sosial tidak akan menyurutkan usaha mereka di bidang usaha sayuran organik.